Bioremediation of petroleum contaminated soil-water resources using neat biodiesel: A review - Gupta P.K.; Mustapha H.I.; Singh B.; Sharma Y.C. (My University, 2025)
Considering the petroleum spill in global space and time, the low-cost remediation and management is the key to address the United Nation's sustainable development goals (SDG), particularly SDG 6 (Clean water and sanitation), SDG 7 (Affordable and clean energy), SDG 13 (Climate action), SDG 14 (Life below water), and SDG (Life on land). This paper reviews the applicability of neat biodiesel (B100) as a biostimulator and its role in bioaugmentation, microbial seeding techniques, for the treatment of diesel and biodiesel blends contaminated soil and groundwater resources. Microbial (Bacterial and fungal) communities have been identified in the soil and groundwater with the ability to degrade petroleum contaminants and its blends with biodiesel. A large number of studies suggest that application of neat B100 can stimulate microbial growth up to 109 cell/g at start-up period of 2–3 weeks, once dehydrogenase activity gets started. Microbes preferentially start degrading the biodiesel in the first instance and thereafter maintain the ability to consume ∼90 % of petroleum constituents. Thus, the successive bioaugmentation with neat B100 as a biostimulant can be a novel strategy to achieve more than 98 % degradation for petroleum compounds. For bioaugmentation, the consortium of Citrobacter, Pseudomonas sp., Candida viswanathii, Gordonia sp., Alcaligenes, Rhodococcus erythoropolis, etc. presents an extraordinary ability to remove diesel, biodiesel, and its blends from polluted soil and groundwater resources. Interestingly, the application of neat biodiesel and also its B20 blend does not alter the indigenous microbial community in the batch scale setups. Taken together, a conceptual model has been presented for the free-phase and dissolved phase petroleum diesel and neat biodiesel and for its low-cost treatment. Recommendations made in this paper could be used in planning, management, and remediation of diesel–biodiesel polluted sites. This article will help to deals with stakeholder concerns associated with the prevention, environmental behavior, and remediation of accidental diesel releases using a low-cost neat biodiesel. © 2022 Elsevier Ltd